Association of anthropometric and obesity indices with abnormal blood lipid levels in young and middle-aged adults - Xiaoling Zhou; Zuoli Zou; Ying Liu; Yuzhong Yan; Jing Wu; Geyao Zhou; Ming Li (Heliyon)
Introduction: Obesity is a known risk factor for dyslipidemia. We aimed to evaluate the association between nine obesity indices and various types of abnormal lipid levels in the young and middle-aged. Methods: From July to November 2022, we distributed health survey questionnaires to the target population in the hospital and collected their biochemical and anthropometric data. Multivariate regression models and Receiver operating characteristic (ROC) curve analysis were used for data analyzing. Results: We collected a total of 1174 complete samples. Among the five blood lipid indexes tested in this study, TG (triglyceride) is most closely related to various body measurements (P < 0.05). WC (Waist circumference) has the greatest risk for abnormal TG levels (OR, 2.61; P < 0.001) and high-density lipoprotein cholesterol (HDL-C) levels(OR, 1.96; P < 0.001).WHR has the greatest risk of abnormal low-density lipoprotein cholesterol (LDL-C) levels (OR, 1.35; P < 0.05) and non-high-density lipoprotein cholesterol levels(OR, 1.59; P < 0.001). ROC curve analyses revealed that all the tested variables gave the highest area under the curve (AUC) values for predicting high TG in comparison to other plasma lipid abnormalities. The AUC of WC, AVI and BMI were 0.81, 0.80 and 0.79 respectively. Conclusion: Specific obesity-related anthropometric measurements, including WC, AVI, and WHR, show improved predictive accuracy in identifying abnormal lipid levels across diverse types. This study supports their effectiveness in early dyslipidemia screening among young and middle-aged individuals.